BIBLIOMETRIC ANALYSIS OF INFORMATION COMMUNICATION TECHNOLOGY RESEARCH IN AGRICULTURAL EXTENSION - Paul Mansingh, J. , Ravikanth Makarla , Nisha, A , Anbarasan, P, Emam Adem Endris (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Information on agricultural technologies is to be shared for the benefit of farmers. The availability of timely information and technology is important for improving the quantity and quality of agricultural production. India has now two decades of experience in using ICTs in agriculture. A lot of improvements in the usage of ICTs have taken place in response to the developments in agricultural technologies and challenges in agriculture. Several initiatives with ICT interventions have been implemented. The researchers worldwide have conducted many research studies in different aspects of ICTs in agriculture and published the research findings in leading peer-reviewed journals. There is a gap in the bibliometric analysis of ICT research in the agricultural extension field. The bibliometric analysis is useful in revealing the research studies carried out in a particular field by identifying the trends in terms of publication, citations, authors, keywords, and institutions. The bibliometric data related to ICT research in the field of Agricultural Extension were downloaded from the Scopus database. VOSviewer was used in analyzing the retrieved data from the Scopus database. More articles were published from India followed by the United States. But, the United States was ahead of India with more citations. The Netherlands top the list with more citations per document. The density visualization revealed that countries such as India, the United States, Nigeria, and the United Kingdom led the research in ICTs in Agricultural Extension. More articles were published by Tufts University (The United States) followed by Wageningen University (The Netherlands) and the National Academy of Agricultural Research Management (NAARM), Hyderabad, India. The author-co-authorship network analysis revealed three clusters with 66 links. The clusters were only 3 that indicate more collaborative research works on ICTs in Agricultural Extension should be undertaken in the future